SPATIAL ASSESSMENT AND REDESIGN OF A GROUNDWATER QUALITY MONITORING NETWORK USING ENTROPY THEORY, GAZA STRIP, PALESTINE - Mogheir Y.; Singh V.P.; De lima J.L.M.P. (My University, 2006)
Using entropy theory, a methodology was developed for the evaluation and redesign of groundwater quality monitoring wells in the Gaza Strip in Palestine. Essential to the methodology is the development of a Transinformation Model (TM) which yields the amount of information transfer and the dependency between the wells as a function of distance. The TM parameters, such as the minimum transinformation and the range, were employed for evaluating the network which revealed that most of the distances between wells were less than the range. It also indicated that a high percentage of redundant information existed in the network. Therefore, the network was reduced by superimposing a square pattern over the monitored area and selecting one well per square block in a stratified pattern. The methodology was tested using the chloride data collected from 1972–2000 from 417 groundwater quality monitoring wells in the Gaza Strip. The number of the groundwater quality monitoring wells in the Gaza Strip was reduced by 53%, while there was 26% redundant information based on the minimum existing distance between wells. This methodology is meant to help monitor the groundwater quality (salinity) in the Gaza Strip.
Keywords: GROUNDWATER MONITORING; ENTROPY THEORY; REDUNDANT INFORMATION; SALINITY; GAZA STRIP